Properties of a transmission assignment algorithm for multiple-hop packet radio networks. - Hammond, J.L (IEEE Transactions on wireless communications)
We study an algorithm, originally defined by Lyui (1991), for assigning collision-free broadcast transmissions for packet radio networks. The method has a number of advantages - it is distributed, fair, permits each terminal to calculate a different frame size, requires only a limited exchange of information, and does not require a contention-based channel-access protocol. These properties make the assignment algorithm particularly useful for dynamic ad hoc networks because the transmission assignments can be easily and quickly adapted to local changes in the topology. An improved description of Lyui's algorithm is given and new simulation results are presented to demonstrate the properties of the transmission assignments for a variety of large networks.